Behavior of Per- and polyfluoroalkyl substances (PFAS) in Pilot-Scale vertical flow constructed wetlands treating landfill leachate. (15th April 2023) - Lott, Dreyton J.; Robey, Nicole M.; Fonseca, Rachel; Bowden, John A.; Townsend, Timothy G.
Graphical abstract: Highlights: Detection of 18 PFAS in diluted landfill leachate. Overall removal of Total PFAS concentrations is limited. Observed decreases in precursor PFAS, increases in terminal PFAS. VFCWs are likely to produce an apparent PFAS increase from a regulatory perspective. Abstract: This study investigated the behavior of per- and polyfluoroalkyl substances (PFAS) in multiple pilot-scale vertical flow constructed wetlands (VFCW) treating landfill leachate. Eight pilot-scale VFCW columns planted with Typha latifolia or Scirpus Californicus were fed untreated municipal solid waste (MSW) landfill leachate that was diluted with potable water at a 1:10 ratio (1 part leachate to 10 parts total) at a fixed daily hydraulic loading rate of 0.525 m d -1 . Ninety-two PFAS were examined and 18 PFAS were detected at quantifiable concentrations (7 precursor species and 11 terminal species). The average concentration of Σ92 PFAS in the influent was 3, 100 ng L -1, which corresponded with minimal reduction in the effluents from the four VFCW (decreases ranged from 1% to 12% on average for Σ18 PFAS); however, precursors 6:3 FTCA, 7:3 FTCA, N-MeFOSAA, and N-EtFOSAA concentrations decreased significantly in the VFCW effluents, and significant decreases in the concentrations of these PFAA-precursors were concurrent with a significant increase in concentrations of five PFAAs (PFBA, PFNA, PFBS, PFOS, and PFOSI). This trend indicates that from a regulatory perspective, standalone VFCWs are likely to produce an apparent PFAS increase, which may also be true for many other leachate treatment processes incorporating aerobic biological treatment. Additional treatment to address PFAS should be integrated prior to the use of any system, including VFCWs, for the treatment of constituents of concern in MSW landfill leachate.